Perception of E-learning among Banaras Hindu University Students: A Comprehensive Analysis - Sukhchain Singh,; Arun Kumar Singh,; Prashish Singh, Prashish Singh; Priyanka Roy, (Indian Journal of Extension Education, 2024)
The COVID-19 pandemic necessitated a transformation in teaching and learning methods, leading to the widespread adoption of E-learning. The study was conducted in 2021, employing a structured questionnaire and descriptive research design to analyze the perception of Banaras Hindu University Students towards E-learning. The survey included 127 respondents, with representation from the Institute of Agricultural Sciences (I.A.S.), Indian Institute of Technology (I.I.T.), Institute of Medical Sciences (I.M.S.), Institute of Management Studies (I. Mg. St.), Institute of Sciences (I. Sc.), and Institute of Environment and Sustainable Development (I.E.S.D.).This perception of students towards E-learning was measured using a 3-point continuum Likert scale consisting of 17 items. The majority of (66.92%) respondents had a favourable perception towards E-learning. Age and parent education level education had a positive and significant relationship with the perception of respondents towards E-learning. It can be concluded that the perception towards E-learning among students of six institutes of BHU is positive and this will be the most important aspect as this only affects the further acceptance or rejection of E-Learning.